Parent-perceived recurrent pain in children: associations with maternal pain, depressiveness, socioeconomic status, and children's behavioural difficulties - Petri, Laura; Poulain, Tanja; Vogel, Mandy; Meigen, Christof; Kiess, Wieland; Hiemisch, Andreas (Frontiers in Pediatrics, 2024)
The current study aimed to examine the potential transgenerational associations between maternal pain and depressiveness and childhood pain, and to explore the associations between the children's difficulties and recurrent pain (defined as pain occurring at least once a month in the previous six month) in healthy children aged 3 to 13 years.We collected Data between 2015 and 2019 as part of the LIFE Child study in Germany and investigated associations of maternal pain and depressiveness, child age, sex, pubertal stage, emotional difficulties, conduct difficulties, hyperactivity/inattention, peer group difficulties, and prosocial skills, and family socioeconomic status with the frequency of parent-perceived headache, backache, and stomachache in a sample of 1850 children (4819 documented visits) using logistic and ordinal regression analyses.Results: Overall, 11.8%, 26.6%, and 45.7% of parents reported their children had recurrent backache, headache, and stomachache, respectively, with 5.5% of children were reported to experience all three types of pain simultaneously. Higher age, female sex, puberty, emotional difficulties, low family socioeconomic status, as well as higher maternal impairment due to pain and maternal depressiveness were significantly associated with more frequent pain.Our study suggests that maternal pain, maternal depressiveness, and lower family socioeconomic status as well as child's emotional difficulties are significantly associated with a higher frequency of recurrent pain in children perceived by their parents.